The Effectiveness of Monitoring the Use of Village Funds (DD) in Development in Ohoi Mataholat, Kei Besar District, Central Maluku Regency - Maulana Zuhri Notanubun; Zainal Abidin Rengifurwarin; Stanislaus Kostka Ohoiwutun (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research is a qualitative descriptive research that aims to determine the Effectiveness of Supervision of Village Fund (DD) Use in Development in Ohoi Mataholat, Kei Besar District, Southeast Maluku Regency and What are the Supporting and Inhibiting Factors. This research was conducted in Ohoi Mataholat, Kei Besa District, Southeast Maluku Regency. Primary data collection was carried out using data collection techniques through interviews, observations, and documentation of a number of informants involved in the Supervision and Use of Village Funds for Development in Ohoi Mataholat, Kei Besar District, Southeast Maluku Regency. The results of the study indicate that although there is supervision carried out by the village government and the community, there are still obstacles in terms of transparency, accountability, and supervisory capacity. Factors such as lack of community understanding, low human resources in supervision, and minimal facilities and infrastructure for implementing supervision are the main obstacles in achieving effective supervision. Therefore, this study recommends the need to increase the capacity of supervisors, more intensive socialization to the community, and increase transparency in reporting the use of village funds. Thus, it is hoped that the use of village funds can be more optimal and provide maximum benefits for village development..